Penilaian Hasil Penyuluhan Kesehatan Gigi dan Mulut Pada Komunitas Alumni Abang None Jakarta Selatan - Taufiq Ariwibowo; Aditya Pratama Sarwono; Sri Ratna Laksmiastuti; Didi Nugroho; Meiny Faudah Amin (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
It is important for everyone, regardless of age, to take into account their dental and oral health to enhance their overall well-being. Dentists have the responsibility of educating the public on proper dental and oral care in order to attain the best possible dental and oral health. Nevertheless, there are still numerous individuals who do not prioritize their dental and oral health. With the aim of fulfilling the Tridharma mission in Community Service, the Faculty of Dentistry at Trisakti University has implemented Public Health Services tha provide counseling on oral and dental health for families, staring with the elderly, general dental health, childrens dental health, and safe medications for families. Through the use of a questionnaire, an increase in knowledge was observed among individuals of different age groups regarding oral health care.